Dignidade planetária no capitalismo humanista - Oliveira, Vanessa Hasson de (2014)
The present thesis has as an objective to deepen the theme of planet dignity, axis of the theorical mark of the Humanistic Capitalism, taking the subject of recognition of planetary dignity as a vector of Brazilian Constitution. In order to do so, this work adopts interdisciplinarity, running through the various disciplines that, somehow, establish the needed conversations to show the interdependence between all that live in, and in this form, are part of the planet in its universality. The proposal takes as its core the theory of autopoiesis systems, gravitating quantum physics, theology and philosophy in search of an original element common to all and everyone that justify the pretension of contributing to an paradigmatic change in Law and society, abandoning the anthropocentric perspective definitely for the establishment of a polycentric biopolitic affirmative, achieving, thus, the spin necessary to surpass the ecological crisis in which the world is drowning in